2018
DOI: 10.3389/fmicb.2018.02630
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus BC5 Interferes With Chlamydia trachomatis Infectivity Through Integrin Modulation in Cervical Cells

Abstract: Lactobacilli play a crucial role in maintaining the ecological equilibrium of the vaginal niche, preventing the colonization of exogenous microorganisms. Although many studies have discussed the mechanisms displayed by lactobacilli in counteracting several urogenital pathogens, a few data are available on the interaction between lactobacilli and Chlamydia trachomatis. This study aimed to elucidate the molecular bases of the interaction among vaginal lactobacilli, the sexually transmitted pathogen C. trachomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Since then, several studies reported the ability of different vaginal Lactobacillus strains such as Lactobacillus brevis or Lactobacillus crispatus to strongly inhibit early phases of C. trachomatis infection as well as its intracellular replication. In particular, several potential mechanisms interfering with C. trachomatis adhesion to host cell have been described, including the increased production of lactate and consumption of glucose, the co-aggregation with EBs, the changes in lipid composition of the cell membrane as well as the modulation of the α5 integrin subunit [70,71,72]. As a further defense mechanism, L. brevis has been demonstrated to inhibit the development of C. trachomatis persistent forms induced by HSV-2 coinfection [70].…”
Section: C Trachomatis Interaction With Host Defense Factorsmentioning
confidence: 99%
“…Since then, several studies reported the ability of different vaginal Lactobacillus strains such as Lactobacillus brevis or Lactobacillus crispatus to strongly inhibit early phases of C. trachomatis infection as well as its intracellular replication. In particular, several potential mechanisms interfering with C. trachomatis adhesion to host cell have been described, including the increased production of lactate and consumption of glucose, the co-aggregation with EBs, the changes in lipid composition of the cell membrane as well as the modulation of the α5 integrin subunit [70,71,72]. As a further defense mechanism, L. brevis has been demonstrated to inhibit the development of C. trachomatis persistent forms induced by HSV-2 coinfection [70].…”
Section: C Trachomatis Interaction With Host Defense Factorsmentioning
confidence: 99%
“…Lactobacilli are the predominant microorganisms in the vaginal microbiota of healthy women that contribute to preventing urogenital and sexually transmitted infections [3][4][5]. The protective role in the vagina is exerted through different mechanisms including: adhesion and permanence on the epithelium (promoted by biofilm formation), competitive exclusion against pathogens, production of antimicrobial compounds and/or modulation of the host's immune response [3,[6][7][8][9]. In this scenario, probiotics or pharmaceuticals containing lactobacilli or their derivatives represent a novel strategy to reconstitute the vaginal microbiota and prevent/treat urogenital infections [10,11].…”
mentioning
confidence: 99%
“…The human vaginal microbiome is dominated by lactobacilli with Lactobacillus crispatus as one of the predominant species (31), which also plays a key role in poultry intestinal health (29) and has been implicated in the maintenance of a healthy status, whereas its absence is correlated with a higher risk of infectious disease (32,33). Moreover, L. crispatus has become an emerging probiotic for women's and poultry health due to its ability to fend off invasive pathogenic bacteria through competitive exclusion, production of antimicrobial compounds and exopolysaccharides (34)(35)(36), and elicitation of a beneficial host immune response (37). However, the genetic basis of the L. crispatus probiotic features remains unknown due to the lack of molecular tools available for this genetically refractory species.…”
mentioning
confidence: 99%